PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK TUTOR SEBAYA BERBANTUAN LEMBAR KERJA SISWA (LKS) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR WEB DESIGN SISWA KELAS XMM1 SMK NEGERI 1 MAS UBUD SEMESTER GENAP TAHUN AJARAN 2011/2012 - Handayani, Eka (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
The main purposes of the research (1) To determine whether the application of the cooperative learning model by the technique of peer tutor with the media of students’ work sheet to improve  the learning activities on Web Design for the second semester of tenth grade students of MM1department  SMK Negeri 1 Mas Ubud. (2) To determine whether the application of the cooperative learning model by the technique of peer tutor with the media of students’ work sheet to improve  learning achievement on Web Design for the second semester of tenth grade students of MM1department  SMK Negeri 1 Mas Ubud. (3) To get the students’ respons toward the application of the cooperative learning model by the technique of peer tutor with the media of students’ work sheet. This reseach was a term of Class Action Reseach with two cycles, then the subject of this research was the  students of the second semester of tenth grade of MM1department  SMK Negeri 1 Mas Ubud in the academic year 2011/2012 that’s consisted of 40 students. While the object this research was the students’ activites and their learning achievement on the Web Design subject. The collecting data on the students’ activities was done by applying the observation  method through the media of students’ work sheet. The data of students’ response was collected by giving the questionaire at the end of the second cycle. The data which were collected then analized with descriptive analysis. The result of research showed that the application of the cooperative learning model by the technique of peer tutor with the media of students’ work sheet could improve  the students’ learning activities and their learning achievement on Web Design at the average of 71,25  with  the active category and became 83,92 with the category of very active and the learning achievement on Web Design at the average of 78,96 by the classical learning achievement standard of 77,50% for the first cycle then became 84,08 by the classical learning achievement standard of 92,50% for the second cycle. The students’ response on the application of the cooperative learning model by the technique of peer tutor with the media of students’ work sheet could be categorized positive with score average of 58,43. Based on the data analysis and the study could be concluded that the application of the cooperative learning model by the technique of peer tutor with the media of students’ work sheet could improve  the students’ learning activities and their learning achievement on Web Design for the second semester of tenth grade students of MM1department SMK Negeri 1 Mas Ubud.